Hubungan Antara Tingkat Stres Dengan Perilaku Merokok Mahasiswa Laki-Laki Fakultas Ilmu Kesehatan Universitas Muhammadiyah Surakarta - Biyanzah Drajad Pamukhti, Bagas; Irdawati, S.Kep.,Ns.,M.Si.Med (2016)
Stress is a physical and psychological reaction to any demands that cause tension and disrupt the stability of daily life. In general, the stress can be classified into three namely physical stress, psychological stress, and socio-economics. In general, the pressure experienced student is psychological pressure in which a student has a variety of academic demands that must be faced. Psychological stress can cause anxiety reactions, upset, sad, aggressive, confused and lack of concentration. Students who can not adjust to the psychological pressure well will tend to seek an outlet towards the negative, one of which is smoking behavior. This study aims to determine the relationship between stress levels and smoking behavior of male students of the Faculty of Health Sciences, University of Muhammadiyah Surakarta. This research method is descriptive correlation with cross sectional approach, this type of research is quantitative research. The population in this study were male students of the Faculty of Health Sciences University of Muhammadiyah Surakarta force in 2013 with a sample of 60 male students using Proportional Random Sampling technique. Collecting data using a questionnaire and checklist were analyzed using the Kolmogorov-Smirnov test correlation. The results showed that most students experience stress 63.3% mild, 35% moderate and 1.7% severe stress whereas students who smoke as much as 46.7% and non-smokers at 53.3% of 60 respondents. The results of correlation test Kolmogorov-Smirnov Kolmogorov-SmirnovZ values obtained for 2.553 with a value of significance (p-value) was 0.001, (0.001 <0.05), then Ho is rejected. The conclusion in this study is there is a relationship between stress levels and smoking behavior of male students of the Faculty of Health Sciences, University of Muhammadiyah Surakarta. This study also demonstrates the value of R square of 0.436, meaning that the level of stress affects smoking behavior of male students amounted to 43.6% and the rest influenced by other factors. Keywords : Stress, Smoking, Students